ANALISIS MASALAH PEMASARAN PRODUK HOME INDUSTRI KERUPUK AMPLANG DI TEMBILAHAN - Aplianti, Sri; Johan, Rina Selva; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Marketing is basically building a brand in the minds of consumers. Where in marketing the product there are still problems faced in marketing. This study aims to determine the marketing problems that arise when marketing the product of home industry in Tembilahan amplang crackers. The population in this study is 9 crackers amplang home industry in Tembilahan and the entire population as sampel.Penelitian carried out in January-March 2016. The object of this study is a home owner in Tembilahan amplang cracker industry. The data analysis technique used is descriptive statistics. The data used is primary data, questionnaires (questionnaire) filled respondents and secondary data obtained through literature studies conducted on the books and records obtained under the related research. From the results of this study concluded that marketing problems faced by home amplang cracker industry in Tembilahan that of many aspects of procedures or rules applicable rules in the market thus hampering the marketing of 88.89% and from the aspect of marketing channel length can cause large costs incurred by 77.78%. Can be seen there are still problems that are found in the market the production.Keywords: Marketing, Marketing Problems, Home Industry.